VELOPHARYNGEAL FUNCTION OF AN APERT'S SYNDROME CHILD WITH CLEFT PALATE - OKA, Masuichiro; TAKENOSHITA, Yasuharu; BEPPU, Kazunori (Pediatric Oral and Maxillofacial Surgery, 1993)
Patient A. I. with Apert's syndrome, a 4-year and 5 month-old Japanese girl was described with velopharyngeal function after palatoplasty. She had palatoplasty on 2-year and 2 month-old at the clinic for Second Oral and Maxillofacial Surgery. Kyushu University Dental Hospital. After operation, she had treated for speech for about 2 years. Now velopharyngeal function was sufficiently good. The causes of good progress were as follow, 1) There were no disturbance of mental development. 2) Roconstructions of soft palate was good. 3) The educations for the mother were effective.